Is mental health status impacted by daytime sleepiness in Junior Collegiate student-athletes? A retrospective study of preparticipation physical exams - Pazik, M.; LaMonica, T.; Farmer, K. W.; Roach, R: P.; Chrabaszcz, S.; Altman, J.; Tipper, N.; Horodyski, M. B. (International Journal of Athletic Therapy & Training, 2025)
Context: Lack of sleep in collegiate student-athletes may lead to decreased athletic and academic performance and longer injury recovery time. Recent research has found a link between decreased mental health status and poor sleep habits in collegiate student-athletes.